Inovação na prestação de serviços públicos: estudo do serviço de laudo pericial - Machado, Filipe Molinar (2014)
Demands of society driving change in the status of action and break paradigms in the form of public service delivery have occurred frequently in many countries. Governance institutions, including therein the public service organizations are facing numerous challenges and must exercise its powers from that context, mainly engaging in continuous innovation processes. However, several studies have attempted to elucidate the mechanisms that influence the innovation process in the public sector, mainly focusing on the utility industry, which needs further studies. Hence, in this case suggest proposed guidelines for collecting and interpreting data on technological innovation, such as the Oslo Manual and the preparation of project indicators and metrics of e-services evaluation. Given this situation, this research aims to evaluate the innovation of a state public service, public safety linked to the official expertise, which has undergone a technological innovation for system migration, making the service of what is usually called e-government. Were adopted qualitative and quantitative research methods, in which data collection was based on the Oslo Manual and the indicators of project metrics and evaluation of e-services. The study gathered the servers of Rio Grande do Skills Institute General South working with the searched service. Quantitative data were processed by statistical analysis and qualitative through content analysis, documentary research and participant observation and not a participant. The expert public service innovation configuration studied showed up in the form of pentagon in this modeling itself as a business management tool showing the importance of technological innovation survey data from public service. Future studies on innovation in the public sector could form the conceptual basis for an institutional adequacy lifting of general innovation data, providing and collaborating, therefore, for specific manuals in the utilities sector.